Experimental investigation of aerodynamic vibrations of solar wing system. Issue 15 (November 2018) - Kim, YC; Tamura, Y; Yoshida, A; Ito, T; Shan, W; Yang, Q
The general characteristics of aerodynamic vibrations of a solar wing system were investigated through wind tunnel tests using an aeroelastic model under four oncoming flows. In total, 12 solar panels were suspended by cables and orientated horizontally. Distances between panels were set constant. Tests showed that the fluctuating displacement increases proportionally to the square of the mean wind speed for all wind directions in boundary-layer flows. Larger fluctuating displacements were found for boundary-layer flows with larger power-law indices. Under low-turbulence flow, the fluctuating displacement increased proportionally to the square of the mean wind speed for wind directions between 0° and 30°, but an instability vibration was observed at high mean wind speed for wind directions larger than 40°. And when the wind direction was larger than 60°, a limited vibration was observed at low mean wind speed and the instability vibration was also observed at high mean wind speed. Fluctuating displacements under grid-generated flow showed a similar trend to that of the boundary-layer flows, although the values became much smaller.